Digestive glycosidases from cannonball jellyfish (Stomolophus sp. 2): identification and temporal-spatial variability - Raul Balam Martinez-Perez; Jorge A. Rodriguez; Miguel A. Cisneros-Mata; Luis Alonso Leyva Soto; Pablo Gortáres-Moroyoqui; Ana Renteria-Mexia; Edna Abigail Hernandez Corral; Lourdes M. Diaz-Tenorio (PeerJ, 2023)
Jellyfish are economically important organisms in diverse countries, carnivorous organisms that consume various prey (crustaceans, mollusks, bivalves, etc.) and dissolved carbohydrates in marine waters. This study was focused on detecting and quantifying the activity of digestive glycosidases from the cannonball jellyfish (Stomolophus sp. 2) to understand carbohydrate digestion and its temporal-spatial variation. Twenty-three jellyfish gastric pouches were collected in 2015 and 2016 in the Gulf of California in three localities (Las Guásimas, Hermosillo, and Caborca). Nine samples were in intra-localities from Las Guásimas. Chitinase (Ch), β-glucosidase (β-glu), and β-N-acetylhexosaminidase (β-NAHA) were detected in the gastric pouches. However, cellulase, exoglucanase, α-amylase, polygalacturonase, xylanase, and κ-carrageenase were undetected. Detected enzymes showed halotolerant glycolytic activity (i = 0–4 M NaCl), optimal pH, and temperature at 5.0 and 30–50 °C, respectively. At least five β-glucosidase and two β-N-acetylhexosaminidase were detected using zymograms; however, the number of proteins with chitinase activity is not precise. The annual variation of cannonball jellyfish digestive glycosidases from Las Guásimas between 2015–2016 does not show significant differences despite the difference in phytoplankton measured as chlorophyll α (1.9 and 3.4 mg/m3, respectively). In the inter-localities, the glycosidase activity was statistically different in all localities, except for β-N-acetylhexosaminidase activity between Caborca and Hermosillo (3,009.08 ± 87.95 and 3,101.81 ± 281.11 mU/g of the gastric pouch, respectively), with chlorophyll α concentrations of 2.6, 3.4 mg/m3, respectively. For intra-localities, the glycosidase activity did not show significant differences, with a mean chlorophyll α of 1.3 ± 0.1 mg/m3. These results suggest that digestive glycosidases from Stomolophus sp. 2 can hydrolyze several carbohydrates that may belong to their prey or carbohydrates dissolved in marine waters, with salinity over ≥ 0.6 M NaCl and diverse temperature (4–80 °C) conditions. Also, chlorophyll α is related to glycosidase activity in both seasons and inter-localities, except for chitinase activity in an intra-locality (Las Guásimas).